KREATIVITAS SENI MEMBATIK MENGGUNAKAN MOTIF BAWA PADA JURUSAN KRIYA KREATIF BATIK DAN TEKSTIL DI SMKN 3 KOTA BIMA - Titin Rahmawati; Roslyn Roslyn (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
Indonesia is a nation rich in cultural and artistic treasures, consisting of several islands, tribes that are very famous around the world by having a diversity of culture and artistic creativity, namely traditional clothes and fabrics typical of their respective regions, one of which is batik. The type of research that will be used is a type of research that is qualitative descriptive